PENGARUH STRATEGI IMAGE STREAMING DALAM PEMBELAJARAN MENULIS CERPEN SISWA KELAS XI SMA - Fauziah, Ika; Mayong, Mayong; Azis, Azis (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2020)
The Effect of Image Streaming Strategies in Short Story Writing Learning in Class XI High School Students. This study aims to describe the short story writing skills of class XI students of SMA Negeri 3 Takalar Regency before and after using the image streaming strategy and to prove the effect of the image streaming strategy on short story writing skills. This type of research is pre-experimental, with the research design of One Group Pretest-Posttest. The data analysis technique used is descriptive and inferential statistics. The results showed that the short story writing skills of students before using the image streaming strategy were classified as less skilled and after using the image streaming strategy were classified as quite skilled, and the image streaming strategy had an effect on students' short story writing skills.